PERAN PEMERINTAH BRAZIL DALAM MENANGANI PENGUNGSI VENEZUELA DI BRAZIL - ", Krismawati; Retnaningsih, Umi O. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Refugee and asylum seeker are big issues for human security. Conflicts in Venezuela forces many people to leave this country to seek better lives in their neighbor country, Brazil. The Brazilian government with Brazilian military and United Nations agencies to help those refugees. High number (48%) of refugees decision to integrate with local people by living in Brazil is interesting. This study examined the roles of those humanitarian organization to foster their decent live while in their estuary in Brazil.This qualitative research adopted pluralism perspectives and analyzed with international cooperation theory from Teuku May Rudy for its role as an actor. Data comes from books, journals, news from BBC and CNN, official documents of UNHCR, articles, and websites.The study showed the Brazilian government and its partners for plays several important roles to settle the problems. Refugees have three options: resettlement, local integration, and voluntary repatriation. Surprisingly 48% choose for local integration. The Brazilian government played initiator role by cooperating with Brazilian military and United Nations agencies to obtain enough funding. As facilitator can fulfill refugees basic need for foods, clear water, health service and medication.  Keywords: Government, Brazilian Military, United Nations Agencies, Role, Refugees, Venezuela, Brazil